St Louis of Toulouse in the Context of Franciscan Iconography on the Portal of St Francis’ Church in Ancona - Kovačević, Marijana (IKON, 2010)
Abstract The paper focuses on the iconography of the monumental portal of St Francis’ Church in Ancona, one of the works of the most important Dalmatian 15th century artist, architect and sculptor Juraj Dalmatinac (Giorgio da Sebenico). The interest of the authoress is mainly concerned with the image of the Franciscan bishop-saint sculpted on that portal, St Louis of Toulouse, especially the way the image of the saint “borrows” the attribute typical of the image of another Franciscan saint, St Anthony of Padua. Namely, instead of covering the saint’s robes with the usual fleur-de-lis, the heraldic sign of the Angevin royal family to which St Louis belonged, the sculptor placed a branch of lily in the saint’s hand as an equivalent attribute. This kind of presentation of St Louis of Toulouse is unparalleled in Franciscan iconography and illustrates the way this imaginative artist merged the presentations of two Franciscan saints so that the result can, placed relatively high on the facade, function as one or the other at the same time. Furthermore, the placement of St Louis in the right baldachine of the top register of the saints on the portal will be considered from the point of view of the usual iconographic topography of St Louis because this particular position of his image seems to be favoured among many Gothic painters whose works, illustrative of this matter, will be, in comparison, brought to attention.